2012
DOI: 10.1097/mcp.0b013e32834f0eaa
|View full text |Cite
|
Sign up to set email alerts
|

Occupational diesel exhaust exposure as a risk factor for chronic obstructive pulmonary disease

Abstract: Purpose of Review Chronic obstructive pulmonary disease (COPD) is a major source of morbidity and mortality worldwide. Although cigarette smoking is the major cause of COPD, occupational exposures have emerged as an important risk factor, especially in nonsmokers. In this review we assess the state of the literature on the association of COPD with a specific occupational exposure, diesel exhaust. Recent Findings A large body of literature links general occupational exposures to dust and fumes with an increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 26 publications
1
29
0
2
Order By: Relevance
“…Among nonsmoking men, the prevalence of COPD ranged from 3.1% in Cape Town, South Africa, to 9.4% in Manila, Philippines [41]. Higher COPD prevalence among nonsmoking women has been associated with increased indoor air pollution because of biomass fuels used at home [18,34,35]. Other studies have shown that development of COPD could result from exposures to second-hand smoke at home or in the workplace [42][43][44].…”
Section: Higher Prevalence Of Chronic Obstructive Pulmonary Disease Imentioning
confidence: 99%
“…Among nonsmoking men, the prevalence of COPD ranged from 3.1% in Cape Town, South Africa, to 9.4% in Manila, Philippines [41]. Higher COPD prevalence among nonsmoking women has been associated with increased indoor air pollution because of biomass fuels used at home [18,34,35]. Other studies have shown that development of COPD could result from exposures to second-hand smoke at home or in the workplace [42][43][44].…”
Section: Higher Prevalence Of Chronic Obstructive Pulmonary Disease Imentioning
confidence: 99%
“…Potential health effects of short-term exposure to diesel exhaust can include irritation of the eyes, nose, throat, and lungs; lightheadedness; headaches; fatigue; nausea; cough; increased mucus; and worsening of allergies and triggering of asthma attacks. (5) Long-term exposure can potentially cause lung cancer (6)(7)(8) ; chronic respiratory disease (9) ; worsening of lung diseases such as asthma, emphysema, and chronic bronchitis (10) ; and heart disease and worsening of pre-existing heart conditions. (11,12) On our site visits in beach areas we observed clouds of fine sand on residential streets that were produced by vehicle movement suspending the sand that remained on the roads.…”
Section: Introductionmentioning
confidence: 99%
“…Such exposures include dust, sea salt, automobile exhaust, industrial emissions, welding fumes, sawdust, animal waste, and crop dust (Seinfeld and Pandis 2012). Exposure to specific aerosols lead to specific adverse health outcomes: Coal mine dust to adverse respiratory changes (Henneberger and Attfield 1997); welding fume to respiratory diseases and lung cancer (Antonini 2003); and diesel fume to pulmonary disease (Hart et al 2012) and lung cancer (Lipsett and Campleman 2000).…”
Section: Introductionmentioning
confidence: 99%